Conceptual frames, rhetorical strategy and divine reciprocity in Matthew 7:1–5 - Nel, Marius (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
This article conducted a comprehensive rhetorical, parabolic, and conceptual frame analysis of the parable in Matthew 7:1–5. It sought to clarify its ethical vision within Matthew’s narrative and socio-historical context. The parable was analysed by using Akpan and Viljoen’s parable methodology, as well as Kazen and Roitto’s measure, accounting, and size conceptual frames to uncover Matthew 7:1–5’s cognitive foundations of moral judgement. The analysis undertaken situated Matthew 7:3–4 within the Sermon on the Mount’s rhetorical argument and indicated that it can be understood as a parable emphasising ethical self-examination. Matthew’s ethics challenge the dominant size frame, advocating universal righteousness that subverted the honour-shame hierarchies. The parable also reflects the measure and accounting frames that consistently demonstrate God’s reciprocal justice throughout the Gospel of Matthew. The parable is thus a directive for fostering healthy inter-community relationships based on Jesus’s counter-cultural emphasis on forgiveness, generosity, and self-criticism which fundamentally reconfigured ancient Mediterranean power dynamics. Contribution: This research provided an original, comprehensive rhetorical, and cognitive frame analysis of Matthew 7:1–5. In addressing this scholarly gap, it deepened our understanding of Matthew’s systematic use of measure, accounting, and size frames, clarifying Jesus’s transformative ethical vision, promoting self-reflection and non-hierarchical relationships.